Violencia de pareja íntima y depresión en mujeres de áreas rurales de la selva peruana: ENDES 2017-2022 - Reátegui García, Martín Ernesto (2024)
Objective: Determine the relationship between intimate partner violence and depression in women of childbearing age from rural areas of the Peruvian jungle, using data from the Demographic and Family Health Survey (ENDES) corresponding to the years 2017-2022. Methods: This is an analytical cross[1]sectional type of study, considering the study population as women of childbearing age from 15 to 49 years old belonging to rural areas of the Peruvian jungle. A final sample of 6558 women was obtained. A score of "PHQ9 Patient Health Questionnaire ≥10" was considered to determine the presence of relevant depressive symptoms compatible with depression. The indicators of intimate partner violence presence were those used by ENDES, and statistical analysis was performed using the binary logistic regression method. Results: A high prevalence of total intimate partner violence was found, with 53.76%. Within the subtypes of IPV, a higher prevalence of women who suffered psychological IPV was found, with 47.96%, followed by physical IPV with 28.61%, and sexual IPV with 6.50%. The prevalence of relevant depressive symptoms was 4.60%. It was found that women who suffered total IPV (ORa: 4.00; CI95%: 2.73-5.81; p < 0.001), physical IPV (ORa: 2.81; CI 95%: 1.98-3.98; p < 0.001), psychological IPV (ORa: 3.05; CI95%: 2.13-4.36; p < 0.001), and sexual IPV (ORa: 3.13, CI95%: 2.00-4.89; p < 0.001) were more likely to suffer from relevant depressive symptoms, and these findings were statistically significant. Conclusions: Women who were victims of any type of intimate partner violence, likewise (physical IPV, psychological IPV, sexual IPV), were more likely to suffer from relevant depressive symptoms.